Sparing of the hippocampus indicates better collateral blood flow in acute posterior cerebral artery occlusion - Förster, Alex; Mürle, Bettina; Kerl, Hans Ulrich; Wenz, Holger; Al-Zghloul, Mansour; Habich, Sonia; Groden, Christoph (International journal of stroke, 2015)
Background: In acute posterior cerebral artery, occlusion involvement of the hippocampus is a common finding. Nevertheless, until today, infarction and ischemic lesion evolution in the hippocampus has not been studied systematically. Aim: Evaluation of hippocampal infarction patterns in posterior cerebral artery occlusion in the very early phase (≤six-hours) and ischemic lesion evolution on follow-up magnetic resonance imaging in relation to collateral blood flow assessed by a magnetic resonance imaging-based approach was conducted. Methods: In 28 patients [mean age 69·4 ± 13·8 years, 19 (67·9%) males, 10 (32·1%) females] with proximal posterior cerebral artery occlusion, magnetic resonance imaging findings were analyzed, with emphasis on hippocampal infarction patterns on diffusion-weighted images and collateralization on dynamic 4D angiograms derived from perfusion-weighted raw images. Results: On initial diffusion-weighted images, we identified all known hippocampal infarction patterns: type 1 (complete) in 6/18 (33·3%) patients, type 2 (lateral) in 10/18 (55·6%) patients, and type 3 (dorsal) and type 4 (circumscribed) in 1/18 (5·6%) patient respectively. On dynamic 4D angiograms, the grade of collateralization was classified as 1 in 9 (32·1%), 2 in 1 (3·6%), 3 in 10 (35·7%), and 4 in 8 (28·6%) patients. On follow-up diffusion-weighted images, we found new ischemic lesions in three and infarction growth in the hippocampus in five patients. Patients with better collateralization (grades 3 and 4) less often had hippocampal infarctions on initial (P = 0·003)/follow-up diffusion-weighted images (P = 0·046) as well as type 1 on initial (P = 0·007)/follow-up diffusion-weighted images (P = 0·005). Conclusions: Involvement of the hippocampus in proximal posterior cerebral artery occlusion is frequently but not obligatorily observed and highly dependent on the extent of collateralization. The same holds true for hippocampal infarction patterns.